THE STRUCTURE OF THE COURSE "FUNDAMENTALS OF THE METHODOLOGY OF THE DEVELOPMENT OF THE ELECTRONIC COURSE IN THE FIELD OF MEDICAL EDUCATION" AFTER THE INTRODUCTION OF DISTANCE LEARNING DUE TO THE WORLD PANDEMIC COVID-19 - Nataliia Lopina ("Scientific Information Agency "Science-technologies-information" LLC, 2020)
The article presents the structure of the e-learning course "Fundamentals of the methodology of the development of the electronic course in the field of medical education", which was developed to improve the skills of teachers of higher medical education in the introduction of distance learning due to COVID-19 pandemic in the world.